Industry-Specific Knowledge Transfer in Audit Firms: Evidence from Audit Firm Mergers in China - He, Xianjie; Kothari, S. P.; Xiao, Tusheng; Zuo, Luo (The Accounting Review, 2022)
ABSTRACT Using a difference-in-differences approach, we examine the effect of industry-specific knowledge transfer on audit performance after a merger of two Chinese audit firms with different levels of expertise in an industry. For clients in an industry audited by both merging audit firms, those audited by the audit firm less specialized in that industry belong to the treatment group, while all other clients belong to the control group. We find an economically significant improvement in audit quality (as reflected in a reduction in financial misstatements) for the treatment group relative to the control group in the same merged audit firm. We show the treatment effect is not driven by changes in auditor incentives or personnel movement and is more pronounced when we expect stronger communication between the less and more specialized auditors after the merger. We caution that our findings are specific to China and may not generalize to other countries. Data Availability: Data used in this study are available from public sources identified in the text. JEL Classifications: M42.